Accelerated Cortical Osteolysis of Metatarsals in Charcot Neuroarthropathy: A Cross‐Sectional Observational Study. (5th November 2019) - Sinacore, David R.; Smith, Kirk E.; Bohnert, Kathryn L.; Gutekunst, David J.; Johnson, Jeffrey E.; Strube, Michael J.
ABSTRACT: Metatarsals are frequent sites of stress and fragility fractures in younger athletic populations and aging older adults. Metatarsal fractures are particularly common in Charcot neuroarthropathy (CN), a complication of diabetes mellitus (DM) and peripheral neuropathy (PN). Neuropathic metatarsal fractures may be caused by an accelerated cortical bone osteolysis and may be reflected as geometric‐derived strength estimates from standard foot radiographs. The purpose of this cross‐sectional study was to determine geometry and strength‐derived estimates of the metatarsals in individuals with DM, PN, and CN compared with younger and older adult controls who were nondiabetic and nonneuropathic. We studied 62 participants: 20 young adult controls (YACs), 22 older adult controls (OACs), and 20 diagnosed with DMPN&CN. From weight‐bearing radiographs, we measured the outer diaphysis diameter and inner marrow diameter at the distal, middle, and proximal diaphysis sites of the second and fifth metatarsal. From these diameters, we derived strength estimates of combined cortical width (CCt.Wi), percent cortical area (%Ct.rA), buckling ratio (BR), moment of inertia (MOI), and section modulus (SM) at each site in both metatarsals. DMPN&CN participants had an accelerated cortical thinning, decreased %Ct.Ar, increased BR, and lower MOI and SM compared with OACs and YACs. The OACs showed age‐related decreases in CCt.Wi and % Ct.Ar, and increased BR. The BR demonstrated significant group × bone × site interaction with the distal fifth metatarsal in the DMPN&CN group having the lowest bone strength. The BR in the distal fifth metatarsal of DMPN&CN participants was 36% and 49% greater than in the OAC and YAC groups, respectively. DMPN&CN participants have lower metatarsal bone strength estimates compared with younger and older adult controls. Standard foot radiographs demonstrate an accelerated cortical osteolysis in DMPN&CN individuals, particularly in the distal fifth metatarsal diaphysis. © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research © 2019 The Authors. JBMR Plus published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.